2013
DOI: 10.1590/s0004-28032013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of N-Ratio in Selecting Patients for Adjuvant Chemoradiotherapy After D2-Gastrectomy

Abstract: -Context -Whether adjuvant chemoradiotherapy may contribute to improve survival outcomes after D2-gastrectomy remains controvertial. Objective -To explore the clinical utility of N-Ratio in selecting gastric cancer patients for adjuvant chemoradiotherapy after D2-gastrectomy. Methods -A retrospective cohort study was carried out on gastric cancer patients who underwent D2-gastrectomy alone or D2-gastrectomy plus adjuvant chemoradiotherapy (INT-0116 protocol) at the Hospital A. C. Camargo from September 1998 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Two previous studies had also reported the potential role of LNR to select patients for adjuvant cXRT after gastric surgery with D2 lymphadenectomy. 20,28 In turn, these findings were consistent with data reported by Kim et al in the phase III ARTIST trial in which the survival benefit of adjuvant cXRT was most pronounced among patients with LNR >0.25. 20 In contrast, Costa Junior and colleagues reported an observational study that found adjuvant cXRT to benefit patients with milder degrees of LN disease (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Two previous studies had also reported the potential role of LNR to select patients for adjuvant cXRT after gastric surgery with D2 lymphadenectomy. 20,28 In turn, these findings were consistent with data reported by Kim et al in the phase III ARTIST trial in which the survival benefit of adjuvant cXRT was most pronounced among patients with LNR >0.25. 20 In contrast, Costa Junior and colleagues reported an observational study that found adjuvant cXRT to benefit patients with milder degrees of LN disease (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…2026,28,39 The present study confirmed that LNR was a strong, independent prognostic indicator of tumor prognosis relative to other risk factors. Two previous studies had also reported the potential role of LNR to select patients for adjuvant cXRT after gastric surgery with D2 lymphadenectomy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Other previous studies also took into consideration the positive N‐ratio . Studies from Nitti et al, Marchet et al, and Wu et al also addressed lymphadenectomy with >15 nodes.…”
Section: Discussionmentioning
confidence: 99%